Thyrotoxic periodic paralysis with normokalemia: a rare case report - Kulkarni, Pranav Ravi; Mohanan, Jagadeesan; I., Mariraj; Suthakaran, Prasanna Karthik (International Journal of Advances in Medicine, 2021)
Thyrotoxic periodic paralysis (TPP) is a rare etiology for muscle paralysis. It is frequently seen in Asian men. Apart from paralysis, most of them are asymptomatic and are devoid of other clinical features of hyperthyroidism. Due to the rarity of this condition, it is often missed and hence fatal. The metabolic derangement seen in TPP is hypokalemia and is thought to be the pathogenesis of the muscle paralysis. Although in rare clinical encounters, patients with TPP may present with normokalemia. The disorder usually presents in the 3rd decade. The cause for mortality in patients with TPP may be due to respiratory muscle paralysis leading to compromise of the respiratory function or refractory arrhythmias due to hypokalemia. Here we report a rare case of TPP with normokalemia.